AMS Standing Committee on New Skills 2009/2010: Report on the results of the expert groups - Wolfgang Bliem; Silvia Weiß; Gabriele Grün (Arbeitsmarktservice Österreich (AMS), 2012)
In October 2009 the Public Employment Service Austria (AMS) set up a Standing Committee on New Skills with the objective of making use of times when companies are characterised by weak capacity utilisation due to the crisis to prepare the labour force (employees in dependent employment as well as job-seekers) on time for coming changes and demands in connection with labour market-policy support measures. The economic and financial crisis in recent years has made it clear in particular that changes and developments which could already be felt before the crisis are now gaining momentum again in the companies. A popular saying used in this connection is that "After the crisis is not before the crisis". The key objective of the AMS Standing Committee on New Skills is to keep pace with the skills and qualifications which will then be required by anticipating these developments at an early stage. Within the Standing Committee so-called specialist groups are being set up, where experts from different occupational fields ("clusters") identify specific short to medium-term skill and qualification requirements in several working rounds. In the period between October 2009 and June 2010 work was started in the following clusters and three workshops each were held: machinery, motor vehicles, metal; chemistry, plastic, new materials; office and administration; tourism and wellness; construction and building ecology. From the discussions about technical or organisational developments, changes of materials or production techniques, as well as changes in customer behaviour, taste preferences or legal framework conditions, conclusions were drawn about skill and qualification requirements and concepts for new or changed continuing education and training programmes elaborated. This report summarises the key results and recommendations of the clusters.
Keywords: 330